(untitled) (NAU Journal of Technology and Vocational Education, 2025)
Teachers hold a pivotal role in societal development, acting as architects of knowledge and shaping the future through the education they provide. This study explored how perceived injustice, poor remuneration, and student’s aggression towards teachers could predict teacher’s intentions to withdraw from the profession. Three hundred science and technology teachers in Lagos State were used as a sample and were selected through multistage sampling technique. Structured questionnaire was used to collect data from the sample. Exploratory and confirmatory factor analyses were done to ascertain the quality of the data collected and compared with the proposed withdrawal intention model. The result of the study revealed that perceived injustice, remuneration, and student’s aggression toward teachers are some of the major causes of secondary school’s teacher’s withdrawal intentions. The result adds to the robustness of the Job-Demand Resource theory and further implications for policymakers, schools, and education institutions.